When the headline is you : an insider's guide to handling the media - Ansell, Jeff, 1955-; Leeson, Jeffrey, 1969- (Jossey-Bass, 2010)
"A former journalist's tips and guidance on how to deal with traditional online media Former award-winning journalist Jeff Ansell provides a how-to guide for executives and other professionals whose high-visibility requires frequent interviews with the media. Drawn from his workshops at Harvard Business School and MIT-Harvard's Public Disputes Program, the author provides tested techniques, tools, and insights for how to respond to all types of media in tough situations. The book also reveals the lessons learned and the pitfalls to avoid by referencing actual news stories from around the world, and provides exercises for readers who wish to sharpen their media-handling skills. Offers guidance for creating meaningful media messages. Shows how to best answer questions on issues where concern is high and trust is low. Written by Jeff Ansell an award-winning journalist and Fortune 500 consultant. Filled with role-playing exercises followed by advice and tips on how to respond successfully. This book provides an essential and real-world resource for navigating the white waters of media relations."-- Anotace od vydavatele
Keywords: mediální komunikace; masová komunikace; masmédia; rozhovor; public relations; communication in mass media; mass communication; mass media; interview; průvodce; guidebooks